Control of Grid-Tied Inverter During Unbalanced Transient Fault - Khanal, Pallavi; Poudel, Prajna; Jangbu Sherpa, Tashi; Karki, Yuvaaraj; Tamrakar, Indraman (KEC Journal of Science and Engineering, 2024)
With increasing use of renewable and clean form of energy, PV systems have become popular due to its versatility and easy implementation. The overall performance of grid-connected PV systems is directly influenced by the performance of grid-tied inverter. Hence, control of grid-tied PV inverter has become a temptation. This project explores the development of grid-connected PV system and optimization of control strategies for grid-tied inverter to ensure its seamless operation and grid stability during transient faults. The transient faults occurring at the inverter side disrupts the normal operation of inverter and even lead to shut down of inverter during faults. Therefore, a control strategy is suggested and developed to control the overvoltage of DC-link capacitor and deliberately functioning and output of grid-tied inverter is improved. This is simply possible by introducing ELC so that the inverter needs not be shut down.